Personality, Occupational Stress and Wellness Among Prison Officers: The Mediating Role of Self Efficacy and Perceived Fairness - Awanis, Ku Ishak (2012)
The aim of this research is to examine issues confronting prison officers at work: i) the level of wellness, occupational stress, personality, self efficacy and perceived fairness of prison officers, ii) the difference in wellness, personality and occupational stress variables according to prison officers’ gender, age and tenure, iii) the relationship between wellness, personality, occupational stress, perceived fairness and self efficacy variables, iv) self efficacy and perceived fairness as possible mediators and lastly, v) the model fit of prison officers’ wellness. Respondents were 417 prison officers from eight prison locations. Multistage sampling technique consisting of stratified random sampling and simple random sampling was used. Descriptive and inferential statistical analyses were performed via Statistical Package for Social Sciences (SPSS) and Analysis of Moments Structures (AMOS). Findings of the study indicated that there were significant correlations between variables in the study. There was a significant difference in wellness according to prison officers’ tenure group. There was also a significant difference in occupational stress according to prison officers’ gender. The study also revealed significant differences in prison officers’ personality domains i.e. neuroticism, extraversion, openness, agreeableness and conscientiousness, according to their gender. Self efficacy and perceived fairness were revealed as mediators. The finding also showed that the model fitted the data after modification. In conclusion, this study had contributed and further enhanced the knowledge about prison officers’ wellness in relation to their personality, occupational stress, self efficacy and perceived fairness specifically in areas pertaining to organizational behavior, and prison management studies in Malaysia.